"It's a much more relaxed atmosphere": Atmospheres of recovery at a peer respite. (August 2020) - Fletcher, Erica Hua; Barroso, Adriane
Abstract: The peer respite model is an emerging model of community mental health support in the United States, yet, it remains understudied and undertheorized in post-asylum geographies and posthuman scholarship on recovery. A focused ethnography sought to address this gap by considering the sensibilities and urgencies that emerged at a peer respite in the U.S. Southwest. More broadly, this paper describes atmospheres of recovery that formed within the space itself, among peer staff who aimed to motivate guests (service users) to acquire social services during their stay and guests who often experienced homelessness. Beyond an anthropocentric, individualized notion of recovery, we describe the spatial arrangements, temporal urgencies, and material scarcities that mediated guests' experiences of their stay and suggest that the peer respite can be understood as a site of transformation that both enables and limits possibilities for feelings of wellbeing and recovery to arise. Highlights: Contributes to post-asylum geographies and an emerging body of literature on posthuman understandings of recovery. Indicates the temporal, spatial, and material engagements of service users and peer staff at a peer respite. Describes atmospheres of recovery that arise within a resource-limited environment.